The existence and nonexistence of positive solutions for second-order Sturm-Liouville eigenvalue problems - Su, H.; Liu, Lishan (Kexue Chubanshe, 2014)
©, 2014, Chinese Academy of Sciences. All right reserved.We consider the existence and nonexistence of positive solutions for secondorder eigenvalue Sturm-Liouville boundary value problem. We shall show there is an interval such that for every ? in this interval, the existence of at least one positive solution to the boundary value problem is guaranteed, moreover there is no solution when ? is appropriate value.